Environmental, social, and governance (ESG) disclosure and firms financial indicators: analysis of semiconductor industry / Raja Adzrin Raja Ahmad, Thilagavathy Palaniappan and Nurul Azlin Azmi - Raja Ahmad, Raja Adzrin; Palaniappan, Thilagavathy; Azmi, Nurul Azlin (UiTM Cawangan Johor, 2023)
Environmental, social, and governance (ESG) disclosure is a set of disclosure that firms make with regard to environmental considerations including corporate policies to preserve the environment, social consideration, and governance. These three key areas are the important pillars of sustainability and ethical consideration. Despite relying on financial reporting, integrating ESG disclosure in decision-making has become a trend among investors. This paper examines the impact of ESG disclosure and firms 'financial indicators among Malaysian Semi conductor firms. This study analyses five semiconductor firms listed in Bursa Malaysia. Data on ESG disclosure and data on the financial indicators were both gathered from the financial statement. This study finds that firms that disclose ESG in their financial report have good financial indicators as an investment in ESG is able to create competitive advantages in firms. Furthermore, the formation of the sustainable committee in the firms is also able to help the firms to structure their ESG investment strategies. Our study provides a benchmark for practitioners on the best practices of ESG disclosure as the sample of the study is among the firms that received FTSE4 Good Bursa Malaysia (F4GBM) Index recognition. Thus, the directors may need to improve their ESG disclosure as this report becomes an integral element of decision making for future investment opportunities among investors. This study is different as this study compared current ESG disclosure to next year's financial performance. This method provides meaningful information as current disclosure will have a significant effect on future performance. Keywords: Environmental, Social and Governance (ESG), Corporate Governance, Competitive Advantages